ANALISA PENGGUNAAN PERANGKAT DIGITAL DALAM PEMBUATAN KOMIK DIGITAL: Chat GPT - Norenza, Zara; Cita Zunurahma, Fathma (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2024)
This research aims to examine content materials by searching for and analyzing the use of three tools, namely Chat GPT, Gemcraft, and Book Creator as tools for developing digital comics. This research involved hands-on testing of all three pieces of software to understand how they are used, as well as focusing on creating useful usage tutorials. This research was conducted at the PIAUD UIN Jakarta Study Program by utilizing the social media Instagram of the UIN Jakarta PIAUD Study Program. The method used in this research is experimental. The data sources for this research use primary data sources and secondary data sources. Primary data sources are Chat GPT, Gemcraft, and Book Creator software. The secondary data source is literature study. The results obtained are that the three software are media that can accommodate the creation of digital comics and can be used as learning resources. The implications in academic activities can be an interesting alternative learning media for students, as well as a form of actualization of digital-based media updates according to changing times.